WHY BEING WELL-KNOWN IS NOT ENOUGH: EXAMINING BRAND IMAGE AND E-MARKETING EFFECTS ON HOSPITAL VISIT INTENTION - Khoerunnisa, Nazwa; Anwar, Tezza Adriansyah; Pratiwi, Nur Pudyastuti (Journal of Business Studies and Management Review, 2026)
The increasing competition in the healthcare industry requires hospitals to strengthen not only service quality but also brand image and digital marketing strategies. This study aims to analyze the influence of brand image and e-marketing on visit intention toward Oetomo Hospital, a private hospital in Indonesia. A quantitative study with a descriptive–verificative approach was conducted. Data were collected through an online questionnaire from 150 respondents who were familiar with Oetomo Hospital but had never visited it. The data were analysed using path analysis with LISREL software. The results show that Oetomo Hospital has a positive brand image, particularly in terms of medical staff professionalism, service speed, and its ability to meet healthcare needs. E-marketing activities are also perceived as effective, supported by an informative website, search engine visibility, and responsive social media management. However, visit intention remains relatively low, especially at the initial intention stage. Partially, brand image does not have a significant effect on visit intention, while e-marketing has a positive and significant influence, although the magnitude of its effect is limited. Simultaneously, both variables explain only a small proportion of the variance in visit intention, indicating that other factors outside the research model play a more dominant role. These findings suggest that digital marketing is more influential than brand image in stimulating visit intention, but it needs to be supported by more contextual and audience-oriented strategies to effectively increase hospital visits.